BP Portugal and Pingo Doce : how can the strategic alliance between BP and Pingo Doce continue to create value? - Cerveira, Cláudia Maia da Cunha (2016)
This dissertation aims to identify what actions could be developed by companies which are operating in mass retail markets, where consumers value more the price instead of product/service differentiation. The fierce competition in grocery and fuel retail motivated the Portuguese retailers to develop new promotional strategies, focused on prices, through joint loyalty programs. However, what drives the retailers’ program success and consumers’ preferences for their services are not only tangible benefits. In Europe, the partnerships among companies, which operate in grocery and fuel industry, have been also a trend. Therefore, analyzing one of the most successful loyalty programs in the UK and Europe alongside with the one develop by the leading companies in Portugal, it is possible to conclude that the association of recognized brands, with aligned organizational values is critical to managing strategic alliances successfully. The diversified offer of benefits, as a consequence of a multi-partner loyalty program is also considered a distinctive factor due to the sustainability for all participants as well as for the program attractiveness for customers. Thus, it is possible to conclude that strategic alliances may provide a competitive advantage to organizations if their actions meet consumers’ expectations, rewarding them appropriately for their loyalty, but also if participating companies are able to manage alliances taking into account the organizations with different expectations and goals.